MAKNA IDEOLOGI DAN BENTUK PROPAGANDA MEDIA ( Studi Semiotika Barthes media Eramuslim dan National Israel Terhadap Kasus Mavi Marmara ) - Mariko Rizkiansyah (Communication, 2013)
After many years, relationship between Turk and Israel are close. But the relation changed tobad after Turk decided to given human aid ship to Palestine. The human aid ship underarrested by Israel before docked. The raid Israel made several crew human aid died. Themoment of the raid Israel known as Mavi Marmara cases. The war of propaganda betweenTurk against Israel have been made. One of their purpose is to created good opinion publicfor their activity. Eramuslim is one of all media Indonesia which is vocal to against the raidfor mavi marmara. While National Israel is one of the media Israel which is consist to madenews about mavi marmara. Beside the News, there some ideology hiding both of news fromEramuslim and National Israel. The Ideology become identity for news Eramuslim andNational Israel,